Deskripsi Pengaruh Model Pembelajaran Think-Pair-Share Terhadap Self-efficacy Matematis Siswa - Andi Nurul Fitriani; Usman Mulbar; Rusli (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2021)
This study aims to determine the description of the influence of think-pair-share learning models on students' mathematical self-efficacy. The subjects of this study were IPS class X students in one of the high schools in Makassar. Taking the subject was done by giving a questionnaire test to students of class X IPS 3, then from these results 6 research subjects are chosen based on existing categories. The instrument used was a self-efficacy questionnaire containing 21 items that corresponded to the dimensions of self-efficacy and lesson plans that were in accordance with the syntax of the think-pairshare learning model. The results of the study showed that self-efficacy of the high category subjects had a good effect. That is because both subjects already have high strength, level, and magnitude dimensions. For self-efficacy, the medium category subject, after giving questions that were not too difficult at the initial meeting and different discussion processes, was able to influence their level dimensions. As for self-efficacy, it is low, because of the motivation given by the teacher and the success of them friends, the strength dimension and level experienced significant changes. However, because both subjects have inability to express opinions even though they have completed the task, so the generality dimension does not experience significant changes. The results of this study to give information about the effect of students' self-efficacy during the learning process so that in the learning process, teachers can help students understand the lessons according to their self-efficacy.